Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2025)
We are delighted to present a diverse collection of articles that delve into the Portuguese employee’s right to disconnect, cybercrime prevention in Arab countries, digital ownership, identity and action in Southeast Asia, digital reputation in Civil Law, AI-evidence in money laundering cases in Mexico, artificial intelligence in cyberspace, ethics in e-Commerce through self-regulation, terrorism in the Sahel Region and Information and Communication Technology, law teaching through audiovisual means, cyberbullying and Internet crimes involving persons with mental disorders, digital transformation in the legal sector.